Caryophyllene-Type Sesquiterpenoids from the Stembark of Aglalia harmsiana and Their Cytotoxic Activity Against MCF-7 Breast Cancer Cells - Hersa Milawati; Desi Harneti; Rani Maharani; Nurlelasari Nurlelasari; Ace Tatang Hidayat; Mohamad Nurul Azmi; Yoshihito Shiono; Unang Supratman (Molekul, 2019)
Sesquiterpenoid is a class of terpenoid compounds that have the most abundant diversity of structures and biological activitiesthat can be found in natural resources. Tropical plants are main source of sesquiterpenoid compounds such as Aglaiagenus belong to Meliaceae family. A. harmsianais a species from Aglaiathat only has few previous researchs.  Therefore, the purpose of this study was to isolate and determine the structure of sesquiterpenoid compounds from stem barkA. harmsianaalong withtheir cytotoxic activity against MCF-7 breast cancer cells. The isolation process begins by extracting powder from A. harmsianastembark using n-hexane, ethyl acetate and methanol. All extracts were evaluated for their cytotoxic activity against MCF-7 breast cancer cells, and n-hexane extractsshowed significant cytotoxic activitywith IC50values of 117.86 µg/mL. Therefore, n-hexane extracts were further separated and purified by various chromatographic techniquesto obtain compounds 1and 2. Compounds 1and 2were elucidated their chemical structures by spectroscopic methods includingIR, NMR, and MS as well as bycomparison of data with literatures and identified ascaryophyllene-typesesquiterpenoids, β-caryophylleneoxide (1) and senecrassidiol (2). Compounds 1and 2were submitted for cytotoxic eveluation on MCF-7 breast cancer cells and as a result, β-caryophyllene oxide (1) showed the stronger activity compared to senecrassidiol (2). These finding indicatedthat the cytotoxic activity of caryophyllene-typesesquiterpenoid areinfluenced by the presence of double bonds and configuration of methyl groups.